THE PRINCIPLE OF TAX NEUTRALITY AND EXTRAFISCALITY IN THE BRAZILIAN TAX REFORM - Uessler, Danielle; Ferreira, Arthur Sandro Golombieski; Ramos, Mariana Matias Ribeiro (Seven Editora, 2026)
This paper aims to analyze whether the principle of neutrality, one of the pillars of the Consumption Tax Reform, is compatible with the extrafiscal function of the tax system, in order to assess whether there is harmony within the context of the new consumption taxation framework introduced by Constitutional Amendment No. 132/2023. The issue arises from the contrast between neutrality, which seeks to avoid economic distortions and ensure a balanced competitive environment, and extrafiscality, expressed mainly through the Selective Tax, which retains the function of influencing behavior through taxation. The research finds that, although the Reform sought to establish a functional separation between the principle of neutrality and the extrafiscal function, relevant risks remain, such as the reduction of space for promotional policies, the rigid crystallization of essentiality, and political pressures for sector-specific benefits. Using the hypothetico-deductive method, it is concluded that neutrality and extrafiscality are not mutually exclusive, but require harmonization through clear criteria to ensure simplicity, economic efficiency, and social justice.DOI: https://doi.org/10.56238/sevened2026.008-047